Natural Killer Cell-Based Immunotherapy in Gynecologic Malignancy: A Review - Uppendahl, Locke D.; Dahl, Carly M.; Miller, Jeffrey S.; Felices, Martin; Geller, Melissa A. (Frontiers in Immunology, 2018)
Harnessing the immune system has proven an effective therapy in treating malignancies. Since the discovery of natural killer (NK) cells, strategies aimed to manipulate and augment their effector function against cancer have been the subject of intense research. Recent progress in the immunobiology of NK cells has led to the development of promising therapeutic approaches. In this review, we will focus on the recent advances in NK cell immunobiology and the clinical application of NK cell immunotherapy in ovarian, cervical, and uterine cancer.